FRI0574-PC Prevalence of the tight hamstring syndrome (THS) in a school population. (23rd January 2014) - Gomez, C.; ramos, S.; Comesaña, M.; Sánchez, L.; Hidalgo, I.; Albadalejo, D.
Abstract : Background: The Tight Hamstring Syndrome (TSH) is a process of unknown aetiology beginning in childhood by which hamstrings muscles lose elasticity. Two degrees can be identified: shortening degree I and II, which may be improved with stretching exercises. Among young people and adults, THS can have repercussions onpelvis –retroversion- and spine -curved spine-. It may also be related to chronic low back pain, spondylolysis, lumbar disc herniations, listhesis, thus, an early detection of THS is essential in order to prevent these pathologies. The only studies about this matter have been carried out on adult sportsmen/women. Objectives: To measure the prevalence of THS in the schoolchildren from an urban hospital catchment area and discover if there is a relationship between THS and obesity among that age group. Methods: A cross-sectional study has been carried out among the third-year primary schoolchildren from a hospital catchment area. All the children in the third year of primary in the public schools in this area (a total of 122) have taken part in this study, prior to obtaining written consent from their parents to join the research. The study has been carried out by four residents by means of collecting anthropometric measurements and conducting THS tests: fingertip-floor, SLR, popliteal angle, lumbo-horizontal (L-H) angle. Some quantitative variables such as age or BMI as well as some qualitative ones like sex or BMI in percentiles or were also measured. For the statistical analysis, averages with a 95% CI, proportions and chi-square test have been used. An interobserver concordance study for the tests of THS has been carried out (Intra-class correlation coefficient) Results: Out of the 122 children studied (55% boys and 45% girls), with an average age of 8, 4 years (CI 95%: 8, 37-8, 49) 49, 1% weren't overweight, 25, 4% were overweight and 25, 4% were obese. THS test results are normal for 42% of the subjects studied, 34% of them have THS degree I and 24% degree II. Therefore, there is a significant relationship (p 0, 02) between both obesity and overweight and THS presence even though this is not directly related to the degree of THS. Conclusions: A high rate of THS degrees I and II has been found among third year primary schoolchildren. There is a significant relationship between overweight and the existence of THS at different degrees. References: Santonja F, Ramos B, Martínez I, Canteras M. Estudio de la cortedad isquiosural en el municipio de Murcia. En: Libro de abstracts del VIII Congreso Europeo de Medicina del Deporte. Granada, 23-27 de octubre, 1995. Hellsing AL. Thightness of Hamstring and Psoas Major Muscles. A prospective study of back pain young men during their military service. Upsale J Med Sci, 1988; 93: 267-276. Reade E, Hom L, Hallum A, Lopopolo R. Changes in popliteal angle measurement in infants up to one year of age, Developmental Medicine and Child Neurology, 1984, 26: 774-780 . Milne RA, Mierau DR. Hamstring Distensibility in the General Population: Relationship to Pelvic and Back Stresses. Journal of Manipulative and Physiological Therapeutics, 1979, 2 (3): 146-150. Santonja F. Exploración clínica y radiográfica del raquis sagital. Sus correlaciones. Murcia: Secretariado de publicaciones e intercambio científico. Univ. Murcia, 1993 (microficha). Disclosure of Interest: None Declared